Simulation for planning timber supply : a review of selected models - Hadi, Yusuf (1987)
Selected simulation models which have been developed for planning timber supply are reviewed. The models selected are those which illustrate the development of timber-supply models in North America, and those developed for application in Malaysia. They are classified into single-pass and iterative simulation models. A single pass model provides a single piece of information for a given set of independent variables. An iterative simulation model approximates an optimal solution by successive iterations starting with a given set of starting points. The prospects of further application of simulation models in Malaysian forestry are discussed.